Islamic Education Reform in the Digital Age: Challenges and Opportunities for a Modern Curriculum - Zahraini Zahraini; Akib Akib; Rosidin Rosidin; Otong Sulaeman (Yayasan Adra Karima Hubbi, 2025)
The rapid advancement of digital technologies has transformed educational practices globally, presenting both challenges and opportunities for Islamic education. This study examines the dynamics of reforming Islamic education curricula to align with the demands of the digital age while preserving core Islamic values. The research aims to explore effective strategies for integrating digital tools and methodologies into Islamic education, ensuring relevance and accessibility for contemporary learners. A qualitative research approach was employed, utilizing document analysis, expert interviews, and focus group discussions with educators, curriculum developers, and digital experts. The findings reveal that while digitalization enhances access to educational resources and fosters innovative teaching methods, it also introduces challenges such as the potential dilution of traditional values and a digital divide among learners. Key outcomes include a framework for a modern Islamic education curriculum that balances technological integration with spiritual and ethical teachings. The study concludes that reforming Islamic education in the digital age necessitates a holistic approach, embracing technology while safeguarding the integrity of Islamic principles. This research contributes to the discourse on modernizing religious education to prepare learners for a rapidly evolving digital landscape.